IMPLIKASI PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN SUB-SEKTOR PERBANKAN GO-PUBLIC DI BURSA EFEK INDONESIA - Suhartono, Suhartono; Susilowati, Dwi; Fikri Ihza Mahendra, M. (Jurnal GeoEkonomi, 2024)
The purpose of this study is to provide empirical evidence of the effect of Profitability, Leverage and Liquidity on the Value of go-public banking sub-sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sampling technique used in this study was purposive sampling with a total of 10 companies that met the criteria for banking sub-sector companies listed on the Indonesia Stock Exchange. The data used in this study are secondary data. The data analysis technique used in this research is multiple linear regression analysis assisted by the SPSS version 25 application. The results showed that simultaneously Return On Assets (ROA), Debt To Asset Ratio (DAR) and Loan To Deposit Ratio (LDR) had a significant effect on Price To Book Value (PBV). Partially ROA has a positive and significant effect on PBV. DAR has a negative and insignificant effect on PBV. LDR has a negative and insignificant effect on PBV.